KEANEKARAGAMAN JAMUR MIKORIZA ARBUSKULAR PADA RIZOSFER TANAMAN KAKAO (Theobroma cacao L) DI KEBUN RAKYAT DESA DOLAGO KABUPATEN PARIGI MAUTONG - Arsih, Desi Wahyuni; Mutmainah, Mutmainah; Rosmini, Rosmini; Ihwansyah, Muh Fadil (Institute of Computer Science (IOCS), 2025)
Mycorrhiza refers to the symbiotic mutualistic relationship between fungi and plant roots, in which both organisms benefit from the interaction. This study aims to analyze the diversity of Arbuscular Mycorrhizal Fungi (AMF) in the rhizosphere of cocoa plants (Theobroma cacao L.). Soil samples were collected using a purposive sampling method, then isolated and identified to the genus level in the Agronomy Laboratory, Faculty of Agriculture, Tadulako University, Palu. Data analysis included the Shannon–Wiener diversity index and dominance index. Based on the identification results, four genera of AMF were found: Racocetra, Funneliformis, Gigaspora, and Claroideoglomus. The diversity index was 1.09, categorized as low, and the dominance index was 0.40, also categorized as low.